Multimedia system model for electrical circuits on android mobile devices. Issue 3 (March 2021) - Kurniadi, D; Fitriani, L; Satria, E; Rahman, A
Abstract: This article aims to design the multimedia system application model of electrical circuits to make it easier for everyone to learn and understand electrical circuits in support of completing the required electrical circuit learning practice activities. The learning material models are designed interactively, which includes basic knowledge about electrical circuits and electrical circuit simulations. The Multimedia Development Life Cycle (MDLC) method is used for the design of this multimedia system. The design phase consists of 6 stages, namely, concept, design, material collecting, assembly, testing, and distribution. The results of the study are the multimedia system application of electrical circuit that mainly can be applied on Android-based mobile devices.